Cement composition, mortar and hardened body
The use of amorphous titanium oxide in cement compositions addresses the challenge of achieving strength at young ages in low temperature environments, while maintaining moderate working time, enhancing the performance of cement-based materials.
Patent Information
- Application Number
- JP2021039955
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-12
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-03-12
AI Technical Summary
Existing cement-based materials struggle to achieve required strength at young ages, especially in low temperature environments, while maintaining moderate working time for ease of handling.
Incorporating amorphous titanium oxide with specific particle size, density, and surface area into cement compositions, along with cement, sudden hard material, gypsum, and lithium carbonate, to enhance strength and working time.
The cement composition with amorphous titanium oxide exhibits improved strength at young ages in both low temperature and room temperature environments, while maintaining a moderate working time, thus addressing the challenges of early strength development and handling ease.
Smart Images

Figure 0007674120000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a cement composition, a mortar and a hardened product used, for example, in the fields of civil engineering and construction. [Background technology]
[0002] In the civil engineering and architectural fields, there is an increasing demand for streamlined construction, and materials that can be put into service quickly are required. One example of such materials is ultra-fast hardening materials.
[0003] For example, an example of an ultra-fast hardening material is a cement-based material that is ultra-fast hardening and has excellent fluidity (see, for example, Patent Document 1). However, in recent years, the demand for more streamlined construction and for responding to new needs have led to an increasing demand for ultra-fast hardening materials. Specifically, in low-temperature environments, the setting performance decreases, making it difficult to meet the required strength at an early age. Therefore, there is a demand for cement-based materials that meet the required strength at an early age even in low-temperature environments. In addition, there is a demand for cement-based materials that have a moderate usable life so as to ensure working time for easy handling, while avoiding excessive working time. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 03-12350 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a cement composition, a mortar and a hardened product which have improved strength at an early age and an appropriate pot life in a low-temperature environment. [Means for solving the problem]
[0006] The present invention has been made to solve the above problems, and the inventors have made various efforts to solve the above problems, and as a result, have discovered that the inclusion of a specific titanium oxide improves the strength at an early age in a low-temperature environment and provides an appropriate usable life, and have thus completed the present invention. The gist of the present invention is as follows. [1] A cement composition comprising cement, a hardening agent, gypsum, lithium carbonate, and amorphous titanium oxide. [2] The cement composition according to [1], wherein the average primary particle size of the amorphous titanium oxide is 0.5 μm or more and 5.0 μm or less. [3] The density of the amorphous titanium dioxide is 2.0 g / cm 3 More than 3.5g / cm 3 The cement composition according to [1] or [2], which is as follows: [4] The Blaine specific surface area of the amorphous titanium dioxide is 5,000 cm 2 / g or more 15,000cm 2 The cement composition according to any one of [1] to [3], wherein the cement composition has a molecular weight of 1.0 to 1.5 μg / g or less. [5] The cement composition according to any one of [1] to [4], wherein the content of the amorphous titanium oxide is 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the cement. [6] The cement composition according to any one of [1] to [5], wherein the content of the lithium carbonate is 1.0 part by mass or more and 10 parts by mass or less per 100 parts by mass of the cement. [7] The cement composition according to any one of [1] to [6], which contains a set retarder. [8] A mortar comprising the cement composition according to any one of [1] to [7] and fine aggregate. [9] A hardened body obtained by using the mortar described in [8]. Effect of the Invention
[0007] According to the present invention, it is possible to provide a cement composition, a mortar, and a hardened body which have improved strength at an early age and an appropriate pot life in a low temperature environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in detail below. Note that parts and % used in this specification are based on mass unless otherwise specified.
[0009] [Cement composition] The cement composition of the present invention contains cement, a hardening agent, gypsum, lithium carbonate, and amorphous titanium oxide.
[0010] (cement) The cement used in the present invention is not particularly limited, and examples thereof include various cements such as normal, early strength, super early strength, low heat and moderate heat, various mixed cements obtained by mixing these cements with blast furnace slag, fly ash and silica fume, environmentally friendly cements (eco-cements) produced using municipal waste incineration ash and sewage sludge incineration ash as raw materials, commercially available fine particle cements, etc. It is also possible to use various cements and various mixed cements in a fine powder form. Also, cements adjusted by increasing or decreasing the amount of components used in normal cements can be used. In the present invention, it is preferable to select ordinary Portland cement or high-early-strength Portland cement from the viewpoints of high fluidity, carbonation resistance, adhesive strength to reinforcing bars, and rust prevention.
[0011] The cement used in the present invention has a Blaine specific surface area of 2,500 cm from the viewpoint of production cost and strength development. 2 / g or more 7,000cm 2 / g or less, and 2 / g or more 6,000cm 2 / g or less is more preferable, and 2 / g or more 4,500cm 2 It is more preferable that the molecular weight is not more than 1 / g. The Blaine specific surface area value is determined in accordance with JIS R 5201 (physical testing method for cement).
[0012] (Sudden hardwood) The cement composition of the present invention contains a hardening agent for the purpose of increasing strength in a short period of time. The hardening agent preferably contains a calcium aluminate compound. The mixing ratio of the calcium aluminate compound in the hardening agent contained in the cement composition of the present invention is preferably 20% or more and 70% or less, more preferably 30% or more and 60% or less, and even more preferably 35% or more and 55% or less. Here, the calcium aluminate compound is a general term for compounds mainly composed of CaO and Al2O3, and is not particularly limited. In the present invention, calcium aluminate having a CaO / Al2O3 molar ratio of 0.75 to 1.5 is used. When the CaO / Al2O3 molar ratio is 0.75 or more, sufficient strength expression can be obtained. Furthermore, when the CaO / Al2O3 molar ratio is 1.5 or less, sufficient fluidity and usable time can be obtained. Specific examples of calcium aluminate compounds include CaO·Al2O3, 12CaO·7Al2O3, 11CaO·7Al2O3·CaF2, 3CaO·Al2O3, 3CaO·3Al2O3·CaSO4, and further, amorphous substances mainly composed of CaO and Al2O3 (for example, CaO-Al2O3-SiO2 compounds). Generally, industrial raw materials contain impurities such as SiO2, MgO, Fe2O3, TiO2, K2O, and Na2O. These impurities can promote the amorphization of calcium aluminate compounds, so it is acceptable for the total amount of these impurities to be present in a range of 20% or less.
[0013] The Blaine specific surface area of the hardening material is 4,000 cm 2 / g or more 9,000cm 2 / g or less, and 2 / g or more 8,500cm 2 / g or less is more preferable, and 5,000 cm 2 / g or more 8,000cm 2 When the Blaine specific surface area value of the rapid hardening material is within the above range, sufficient rapid hardening is easily obtained, and strength development at low temperatures is also easily obtained. The Blaine specific surface area of the rapid hardening material is determined in the same manner as the Blaine specific surface area of the cement described above.
[0014] The content of the hardening agent is preferably 40 parts by mass or more and 90 parts by mass or less, more preferably 45 parts by mass or more and 85 parts by mass or less, and even more preferably 50 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of cement. By having the content of the hardening agent within the above range, good early strength development is easily obtained, and a decrease in long-term strength is also less likely to occur.
[0015] (plaster) The cement composition of the present invention contains gypsum for the purposes of making it easier to design a long pot life and for the purposes of improving operability. The gypsum used in the present invention is not particularly limited, and examples thereof include anhydrous gypsum, hemihydrate gypsum, and dihydrate gypsum. In terms of strength development, anhydrous gypsum is preferred. More specifically, anhydrous gypsum produced as a by-product of hydrofluoric acid and natural anhydrous gypsum can be mentioned. Furthermore, the gypsum may be used alone or in combination of two or more types.
[0016] The Blaine specific surface area of gypsum is 3,000 cm 2 / g or more, and 2 / g or more is more preferable, and 4,000 cm 2 / g or more. When the Blaine specific surface area of the gypsum is equal to or more than the above lower limit, good early strength development can be obtained. In addition, the Blaine specific surface area of the gypsum is preferably 30,000 cm 2 / g or less, and 2 / g or less, and more preferably 20,000 cm 2 When the Blaine specific surface area value of the gypsum is equal to or less than the above upper limit, a good pot life can be obtained.
[0017] The content of gypsum is preferably 30 parts by mass or more and 70 parts by mass or less, more preferably 35 parts by mass or more and 65 parts by mass or less, and even more preferably 40 parts by mass or more and 60 parts by mass or less, relative to 100 parts by mass of cement. When the content of gypsum is within the above range, it is possible to improve the initial strength development and the pot life.
[0018] (Lithium Carbonate) The cement composition of the present invention contains lithium carbonate for the purpose of accelerating the hardening of the composition and realizing strength development in a short time. Lithium carbonate accelerates the hardening of calcium aluminate compounds in the hardening agent, improving the early strength development. It is known that lithium salts other than lithium carbonate also accelerate the hardening of calcium aluminate, but when lithium salts other than lithium carbonate are used, it is not possible to fluidize the composition and the pot life cannot be secured.
[0019] The content of lithium carbonate is preferably 0.5 parts by mass or more and 10 parts by mass or less, more preferably 1.0 parts by mass or more and 7.5 parts by mass or less, and even more preferably 1.5 parts by mass or more and 5.0 parts by mass or less, relative to 100 parts by mass of cement. By having the content of lithium carbonate within the above range, it is possible to improve the initial strength development and the pot life.
[0020] (amorphous titanium dioxide) The amorphous titanium oxide used in the present invention is amorphous with an irregular structure that does not have a regular atomic arrangement. The amorphous titanium oxide used in the present invention refers to titanium oxide that does not have crystallinity, and has a certain degree of range in terms of crystallinity. That is, the range of crystallinity of amorphous titanium oxide ranges from completely amorphous titanium oxide in which no crystal structure is optically confirmed, but no crystallinity peak is confirmed by X-ray diffraction, to titanium oxide in which a broad crystallinity peak is confirmed. The amorphous titanium dioxide used in the present invention can promote hydration reactions at low temperatures and at an early age, and can improve the strength of the concrete at an early age in a low-temperature environment. The amorphous titanium dioxide used in the present invention can also improve the strength of the concrete at an early age not only in a low-temperature environment, but also in a normal temperature environment. In this specification, a low-temperature environment means an environment in which the concrete composition is poured at 5°C or lower. The amorphous titanium oxide used in the present invention can be obtained, for example, by the chlorine method and the sulfuric acid method. In the chlorine method, the raw material rutile ore is reacted with coke and chlorine to convert it into gaseous titanium tetrachloride, which is then cooled to a liquid state, and then reacted with oxygen at a high temperature to separate the chlorine gas, thereby obtaining amorphous titanium oxide. In the sulfuric acid method, the raw material ilmenite ore is dissolved in concentrated sulfuric acid, and the iron impurity is separated as iron sulfate, which is converted into titanium oxysulfate, which is hydrolyzed to convert it into titanium oxyhydroxide and precipitated, and the precipitate is washed, dried, and calcined to obtain amorphous titanium oxide.
[0021] The average primary particle size of the amorphous titanium oxide is preferably 0.5 μm or more and 5.0 μm or less, more preferably 0.7 μm or more and 4.0 μm or less, and even more preferably 0.9 μm or more and 3.0 μm or less. By having the average primary particle size of the amorphous titanium oxide within the above range, the hydration reaction at an early age can be promoted, and the appropriate fluidity of the cement composition can be obtained. The average primary particle size of amorphous titanium oxide can be determined as the particle size (median size) at which the cumulative volume in the particle size distribution is 50% using a laser type particle size distribution measuring device.
[0022] The density of amorphous titanium dioxide is 2.0 g / cm 3 More than 3.5g / cm 3 It is preferable that the density is 2.2 g / cm or less. 3 More than 3.3g / cm 3 More preferably, it is 2.4 g / cm or less. 3 More than 3.1g / cm 3When the density of the amorphous titanium oxide is within the above range, the hydration reaction at an early age can be promoted, and the cement composition can have an appropriate fluidity. The density of amorphous titanium dioxide can be determined by the gas displacement method. Specifically, the sample chamber containing the sample is pressurized, a valve is opened to diffuse the gas into the expansion chamber, the volume of the sample is calculated from the resulting pressure change, and the density can be calculated by dividing the sample weight by the sample volume.
[0023] The Blaine specific surface area of amorphous titanium dioxide is 5,000 cm 2 / g or more 15,000cm 2 / g or less, and 2 / g or more 12,500cm 2 / g or less is more preferable, and 6,000 cm 2 / g or more 10,000cm 2 When the Blaine specific surface area value of the amorphous titanium oxide is within the above range, the hydration reaction can be promoted at an early material age. The Blaine specific surface area of amorphous titanium oxide can be determined in the same manner as for the Blaine specific surface area of cement.
[0024] The content of amorphous titanium oxide is preferably 0.3 parts by mass or more and 30 parts by mass or less, more preferably 0.4 parts by mass or more and 20 parts by mass or less, and even more preferably 0.5 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of cement. By keeping the content of amorphous titanium oxide within the above range, the hydration reaction at an early age can be promoted.
[0025] (Retarder) The cement composition of the present invention preferably contains a set retarder for the purpose of adjusting the pot life of the cement composition slurry. Examples of the setting retarder include inorganic setting retarders and organic setting retarders. Examples of the inorganic setting retarder include phosphates, silicofluorides, copper hydroxide, boric acid or a salt thereof, zinc oxide, zinc chloride, zinc carbonate, and the like. Examples of organic setting retarders include oxycarboxylic acids (anhydrous citric acid, gluconic acid, malic acid, tartaric acid, glucoheptonic acid, oxymalonic acid, lactic acid, etc.) or their salts (sodium salts, potassium salts, etc.), and sugars such as sugar. The setting retarder may be one or more of these. Furthermore, a mixture of an inorganic setting retarder such as carbonate, bicarbonate, nitrate, hydroxide, silicate, etc. and the above-mentioned oxycarboxylic acid or its salt may be used. Among these, the oxycarboxylic acid or its salt alone, or a mixture of an inorganic setting retarder and a oxycarboxylic acid or its salt is preferred.
[0026] The content of the retarder is preferably 0.5 parts by mass or more and 10.0 parts by mass or less, more preferably 1.0 parts by mass or more and 7.5 parts by mass or less, and even more preferably 1.5 parts by mass or more and 5.0 parts by mass or less, relative to 100 parts by mass of cement. By having the content of the retarder within the above range, it becomes easy to adjust the pot life to the required value, and the hardening time does not become too long, making it difficult for poor hardening to occur.
[0027] The cement composition of the present invention may contain, within a range that does not adversely affect performance, one or more of the following admixtures: expansive agents, gas foaming substances, water reducing agents, air entraining agents, rust inhibitors, water repellents, antibacterial agents, colorants, antifreeze agents, limestone fine powder, slowly cooled blast furnace slag fine powder, sewage sludge incineration ash and its molten slag, urban waste incineration ash and its molten slag, and pulp sludge incineration ash; defoamers, thickeners, shrinkage reducing agents; fibrous substances such as steel fiber, vinylon fiber, carbon fiber, and wollastonite fiber; polymers; clay minerals such as bentonite and sepiolite; and anion exchangers such as hydrotalcite.
[0028] In the cement composition of the present invention, the method of mixing each material is not particularly limited, and each material may be mixed at the time of application, or a part or all of the materials may be mixed in advance. As the mixing device, any existing device such as a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, and a Nauta mixer can be used.
[0029] [mortar] The mortar of the present invention contains the above-mentioned cement composition of the present invention and fine aggregate.
[0030] (fine aggregate) The chemical components of the fine aggregate used in the present invention preferably include a CaO ratio of 85 mass% or more and a SiO2 ratio of 0.2 mass% to 15 mass%. By having the CaO ratio and the SiO2 ratio within the above ranges as the chemical components of the fine aggregate, an ultra-fast hardening grout material having high fluidity, carbonation resistance, adhesive strength with reinforcing bars, and rust prevention properties can be obtained. The proportion of CaO is preferably 87% by mass or more, more preferably 89% by mass or more, and even more preferably 91% by mass or more. The upper limit of the proportion of CaO is not particularly limited, but is preferably 99% by mass or less, and more preferably 98.5% by mass or less. The proportion of SiO2 is preferably 0.25 mass % or more and 13 mass % or less, more preferably 0.3 mass % or more and 11 mass % or less, and further preferably 0.4 mass % or more and 10 mass % or less. In order to make the chemical composition of the fine aggregate fall within the above range and the range described below, silica sand, calcite, scapolite, which is a metamorphic rock, quartz, which is an igneous rock, potassium feldspar, etc. are mixed and prepared. The chemical composition is adjusted by mixing each rock while checking with fluorescent X-ray diffraction so that it falls within the range of the present invention. The chemical composition of the fine aggregate used in the present invention is calculated in terms of oxides.
[0031] The fine aggregate used in this invention has the following chemical components: KO, SO 3、It is preferable that the fine aggregate contains Fe2O3 and Al2O3. 3、 The inclusion of Fe2O3 and Al2O3 contributes to high fluidity, carbonation resistance, adhesion strength to rebar, and rust prevention. The proportion of K2O is preferably 40 ppm or more and 3,000 ppm or less, more preferably 50 ppm or more and 2,500 ppm or less, even more preferably 60 ppm or more and 2,250 ppm or less, and even more preferably 70 ppm or more and 2,000 ppm or less. The proportion of SO3 is preferably 40 ppm or more and 3,000 ppm or less, more preferably 50 ppm or more and 2,500 ppm or less, even more preferably 60 ppm or more and 2,250 ppm or less, and even more preferably 70 ppm or more and 2,000 ppm or less. The proportion of Fe2O3 is preferably 0.1 to 3.0 mass%, more preferably 0.13 to 2.5 mass%, and even more preferably 0.15 to 2.0 mass%. The proportion of Al2O3 is preferably 0.1 to 3.0 mass%, more preferably 0.13 to 2.5 mass%, and further preferably 0.15 to 2.0 mass%.
[0032] The fine aggregate used in the present invention preferably has a reduction in the coarse aggregate ratio of 70% or more and 100% or less, more preferably 75% or more and 99% or less, even more preferably 80% or more and 98% or less, and even more preferably 85% or more and 97% or less, according to JIS A1121 "Abrasion test of coarse aggregate by Los Angeles tester". By reducing the coarse aggregate ratio of the fine aggregate to the above lower limit or more, the adhesion force with the reinforcing bar can be improved. By reducing the coarse aggregate ratio of the fine aggregate to the above upper limit or less, the carbonation resistance can be improved, which contributes to reducing the rusting of the reinforcing bar due to carbonation. In this specification, the "coarse aggregate ratio of the fine aggregate" refers to a value obtained from the result of sieving, and is an index indicating the approximate value of the size of the fine aggregate. In this specification, the "reduction in the coarse aggregate ratio of the fine aggregate" refers to the ratio of reduction in the coarse aggregate ratio after the test, comparing the coarse aggregate ratio before the test and the coarse aggregate ratio after the test, in the abrasion test of coarse aggregate by Los Angeles tester. In order to bring the reduction in the coarse aggregate ratio of the fine aggregate within the above range, silica sand, calcite, scapolite, which is a metamorphic rock, quartz, which is an igneous rock, potassium feldspar, etc. are mixed and prepared. The reduction in the coarse aggregate ratio of the fine aggregate is adjusted by mixing each rock while checking it by abrasion test of coarse aggregate using a Los Angeles tester so that it falls within the range of the present invention. As long as the reduction in the coarse aggregate ratio of the fine aggregate is within the above range, the place of production or the origin of the fine aggregate is not particularly limited.
[0033] The content of the fine aggregate is preferably 40 parts by mass or more and 300 parts by mass or less, more preferably 75 parts by mass or more and 250 parts by mass or less, and even more preferably 100 parts by mass or more and 200 parts by mass or less, relative to 100 parts by mass of cement. By having the content of the fine aggregate be equal to or more than the lower limit, the amount of heat generated can be reduced, shrinkage can be suppressed, and cracks can be suppressed. In addition, by having the content of the fine aggregate be equal to or less than the upper limit, a mortar having high fluidity, carbonation resistance, adhesion strength to reinforcing bars, and rust prevention properties can be obtained.
[0034] The mortar of the present invention is made by kneading a cement composition, fine aggregate, and water. The amount of mixing water in the present invention is not particularly limited because it varies depending on the purpose and application of use and the content ratio of each material, but is preferably 10 parts by mass or more and 70 parts by mass or less, more preferably 14 parts by mass or more and 65 parts by mass or less, and even more preferably 16 parts by mass or more and 60 parts by mass or less, relative to 100 parts by mass of the cement composition. By making the amount of mixing water equal to or more than the above lower limit, it is possible to suppress the decrease in fluidity and to suppress the heat generation from becoming extremely large. In addition, by making the amount of mixing water equal to or less than the above upper limit, it is possible to ensure the strength development.
[0035] In the present invention, the method for mixing the cement composition, fine aggregate, and water is not particularly limited, but it is preferable to use a hand mixer with a rotation speed of 900 rpm or more, a normal high-speed grout mixer, or a twin-shaft forced mixer.
[0036] For mixing with a hand mixer or high-speed grout mixer, it is preferable to put a certain amount of water in a container such as a pail or a mixer in advance, then add the cement composition and fine aggregate while rotating the mixer, and mix for 3 minutes or more. For mixing with a forced mixer, it is preferable to put the cement composition and fine aggregate in advance, add a certain amount of water while rotating the mixer, and mix for at least 4 minutes. If the mixing time is shorter than the specified time, the mortar may not have a proper fluidity due to insufficient mixing. The mixed mortar is usually pumped to the application site using a manual injection gun, a diaphragm type hand pump, or a squeeze type mortar pump, and then filled and applied to form a hardened body using the mortar of the present invention. EXAMPLES
[0037] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0038] The present invention will be specifically described below with reference to each example.
[0039] <Materials used> Cement: Ordinary Portland cement, Blaine value 3,300 cm 2 / g, commercially available Rapid hardening material: amorphous, calcium aluminate with the main component 12CaO·7Al2O3, Blaine value 6,000 cm 2 / g Gypsum: anhydrous gypsum, Blaine value 5,000 cm 2 / g Lithium carbonate: commercially available Titanium oxide (A): amorphous, average primary particle size 1.65 μm, density 2.90 g / cm 3 , Blaine value 7,800 cm 2 / g, commercially available Titanium dioxide (B): crystalline, anatase type, average primary particle size 2.69 μm, density 3.92 g / cm 3 , Blaine value 5,800 cm 2 / g, Kishida Chemical Co., Ltd., Reagent Titanium dioxide (C): crystalline, anatase type, average primary particle size 4.62 μm, density 3.90 g / cm 3 , Blaine value 11,000 cm 2 / g, Wako Pure Chemical Industries, Ltd., Reagent Titanium dioxide (D): Crystal, rutile type, average primary particle size 1.21 μm, density 4.13 g / cm 3 , Blaine value 8,000 cm 2 / g, Wako Pure Chemical Industries, Ltd., Reagent · Retarder: Anhydrous citric acid, commercially available
[0040] <Test Method> Gel time: The gelation of the cement composition was measured by temperature. The cement composition prepared in each Example and Comparative Example was placed in a cup, and the gel time (working time) was determined as the time when the temperature rose by 2°C from the mixing temperature. Compressive strength: Compliant with JIS R 5201. The test specimen size was φ40mm x 160mm, and evaluation was performed on specimens aged 1 hour and 3 hours.
[0041] [Example 1] A cement composition comprising titanium oxide as shown in Table 1 was prepared for 100 parts by mass of cement. In this case, 35 parts by mass of mixing water was used for 100 parts by mass of the cement composition. The gelation time and compressive strength were measured at environmental temperatures of 5°C and 20°C. The results are shown in Table 1.
[0042] [Example 2~ 8 , Comparative Examples 1 to 5 、Reference Examples 1~3 ] A cement composition was prepared in the same manner as in Example 1, except that the blend ratio was changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0043] [Table 1]
[0044] From Table 1, it is clear that the cement composition containing amorphous titanium oxide has good strength at an early age not only in room temperature environments but also in low temperature environments, and has an appropriate pot life. [Industrial Applicability]
[0045] By using the concrete composition of the present invention, the strength at an early age in a low-temperature environment is good, and since it has an appropriate pot life, it can be suitably poured in a low-temperature environment.
Claims
1. The composition contains cement, a hardening agent, gypsum, lithium carbonate, and amorphous titanium oxide, The content of the hardening agent is 45 parts by mass or more and 90 parts by mass or less relative to 100 parts by mass of cement, The content of the gypsum is 30 parts by mass or more and 70 parts by mass or less relative to 100 parts by mass of cement, The content of the lithium carbonate is 1.5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of cement, A cement composition, wherein the content of the amorphous titanium oxide is 0.5 parts by mass or more and 12 parts by mass or less per 100 parts by mass of cement.
2. 2. The cement composition according to claim 1, wherein the average primary particle size of the amorphous titanium oxide is 0.5 μm or more and 5.0 μm or less.
3. The density of the amorphous titanium oxide is 2.0 g / cm 3 3.5g / cm or more 3 3. The cement composition according to claim 1 or 2, wherein:
4. The Blaine specific surface area of the amorphous titanium oxide is 5,000 cm 2 / g or more 15,000cm 2 The cement composition according to any one of claims 1 to 3, wherein the Cement content is 1 / g or less.
5. The cement composition according to any one of claims 1 to 4, which contains a set retarder.
6. A mortar comprising the cement composition according to any one of claims 1 to 5 and fine aggregate.
7. A hardened body obtained by using the mortar according to claim 6.
Citation Information
Patent Citations
Ultra-rapid-setting cement composition
JP1991012350A
Cement composition
JP2000219564A
Injection material and structure using the same
JP2002201056A
Injection material for improving ground
JP2003193051A
Premixed mortar
JP2006056730A